A metallic superhard boron carbide: first-principles calculations. Issue 15 (21st April 2015) - Ma, Mengdong; Yang, Bingchao; Li, Zihe; Hu, Meng; Wang, Qianqian; Cui, Lin; Yu, Dongli; He, Julong
<x xml:space="preserve">Abstract</x> This work proposed a new metallic, superhard phase of BC3 which might exist in experimentally synthesized BC3.